Algebra: A Combined Approach (4th Edition)

Published by Pearson
ISBN 10: 0321726391
ISBN 13: 978-0-32172-639-1

Chapter 5 - Section 5.2 - Negative Exponents and Scientific Notation - Exercise Set: 66

Answer

$\dfrac{(rs)^{-3}}{(r^{2}s^{3})^{2}}=\dfrac{1}{r^{7}s^{9}}$

Work Step by Step

$\dfrac{(rs)^{-3}}{(r^{2}s^{3})^{2}}$ Evaluate the exponential expressions in the numerator and the denominator: $\dfrac{(rs)^{-3}}{(r^{2}s^{3})^{2}}=\dfrac{r^{-3}s^{-3}}{r^{4}s^{6}}=...$ Evaluate the division and simplify: $...=r^{-3-4}s^{-3-6}=r^{-7}s^{-9}=\dfrac{1}{r^{7}s^{9}}$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.